Efficient adsorption of methyl orange and methyl blue dyes by a novel triptycene-based hyper-crosslinked porous polymer. Issue 9 (16th February 2022) - He, Yan; Bao, Wenli; Hua, Yingcen; Guo, Zhulei; Fu, Xiaolei; Na, Bing; Yuan, Dingzhong; Peng, Changjun; Liu, Honglai
Abstract : A novel triptycene-based hyper-crosslinked porous polymer was developed for the highly efficient entrapment of organic dyes from aqueous solution. Abstract : It is still a great challenge to develop new materials for the highly efficient entrapment of organic dyes from aqueous solution. Herein, a novel triptycene-based hyper-crosslinked porous polymer (TPP–PP) was designed and synthesized by a simple Friedel–Crafts reaction. The obtained polymer TPP–PP has a high surface area, abundant pore structure and stable thermal performance. Due to the above characteristics, TPP–PP has good adsorption performance for anionic methyl orange solution (MO) and cationic methyl blue solution (MB). Under the optimal experiment conditions, the TPP–PP showed an excellent adsorption capacity for MO (220.82 mg g −1 ) and MB (159.80 mg g −1 ), respectively. The adsorption kinetics fitted the pseudo-second-order model. The adsorption of MO by TPP–PP reaches equilibrium within 180 minutes, and the adsorption of MB reaches equilibrium within 150 minutes. The adsorption behavior was not only spontaneous but also endothermic in reality. At the same time, TPP–PP also has good reusability. After 5 cycles of experiments, the removal rate of MO and MB by TPP–PP can still reach more than 80%. Thus, the Friedel–Crafts reaction crosslinked method might be a promising approach for the synthesis of novel material for the highly efficient extraction of dye wastewater.